Distributive mixing in a corotating twin screw channel using Lagrangian particle calculations. Issue 6 (3rd October 2017) - Xu, Baiping; Yu, Huiwen; Turng, Lih‐Sheng
Abstract: This work is devoted to the development of a new mapping method for the numerical simulation of melt flow in the complicated forward conveying element of a corotating twin screw extruder under the assumption of periodic boundary conditions of inlet and outlet. The mesh superposition technique (MST) provided by the commercial computational fluid dynamics (CFD) software POLYFLOW was used to deal with the internal moving screw elements, and the flow field of polymer melt obeying the Bird–Carreau constitutive model on the fixed meshes of the flow domain was further solved. After inputting the exported data of the flow field from POLYFLOW, the self‐developed code was further used to characterize the mixing behavior at a finite time under different rotation speeds of the screw elements. A novel mapping method was proposed to convert the instantaneous flow field at the initial time point into the velocity field at any time point. Advection evolution of passive particle groups was simulated by a fourth‐order Runge–Kutta tracking method, and the corresponding variance index was also calculated. The effect of screw rotation speed on distributive mixing was examined. The results showed that the mixing was highly dependent on the initial position whether the particle groups were first placed close to or far away from the intermeshing zone.